Differences in maternal characteristics and their associations with breastfeeding attitudes among primiparous mothers - Mohd Shukri, Nurul Husna; Wells, Jonathan; Fewtrell, Mary (Elsevier, 2021)
Background: The benefits of breastfeeding are well documented, yet substantially below half of all mothers globally meet the recommendation to exclusively breast-feed for 6 months. Objective: This study aimed to examine whether there were differences in maternal factors, including maternal characteristics and breastfeeding attitudes, between those who were eligible versus non-eligible to be included in a randomised trial, as= exclusive breastfeeding was the eligibility criteria for the trial. It also aimed to investigate associations between maternal factors and breastfeeding attitudes. Method: Primiparous pregnant mothers (n=88) completed questionnaires on demographic factors including maternity care and breastfeeding attitude using self-administered questionnaire and Iowa Infant Feeding Attitude Scale (IIFAS). Two weeks post-birth, mothers were screened for eligibility to be included in a randomised trial including assessing for exclusive breastfeeding (EBF). Findings were compared between inclusion (all EBF mothers) and exclusion groups (non-EBF). Results: Inclusion group mothers were significantly younger than those in the exclusion group (26.7±2.8 v 28.5±2.5, p=0.007) and the majority had their husband as the primary maternity care person after birth (X2=12.8, p=0.01). Inclusion group mothers had a more positive perception toward breastfeeding in public and at work on the IIFAS scale (p<0.05). The overall IIFAS score was positively associated with higher breastfeeding confidence (r=0.285, p=0.008), education levels (r=0.31, p=0.003), household income (r=0.32, p=0.003), and age (r=0.28, p=0.008). Conclusion: EBF mothers (inclusion group) tend to be younger, had husband as primary care, and have more positive perception towards breastfeeding outside home. Overall, maternal characteristics and paternal support could influence breastfeeding practices and should be targeted for future intervention. Maternal attitude and perceptions about breastfeeding in public could be improved to encourage exclusive breastfeeding.